2005
DOI: 10.1002/hbm.20143
|View full text |Cite
|
Sign up to set email alerts
|

fMRI‐constrained MEG source imaging and consideration of fMRI invisible sources

Abstract: Recent studies on multimodal brain source imaging have shown that the use of functional MRI (fMRI) prior information could enhance spatial resolution of magnetoencephalography (MEG), while MEG could compensate poor temporal resolution of fMRI. This article deals with a multimodal imaging method, which combines fMRI and MEG for enhancing both spatial and temporal resolutions. Recent studies on the combination of fMRI and MEG have suggested that the fMRI prior information could be very easily implemented by just… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The reduction in the signal-to-noise ratio per source element due to cancellation may result in some active areas being detected with fMRI but not with EEG or MEG. This appears not to be a serious problem, however, for approaches in which fMRI is used to suggest likely locations for the EEG and MEG sources: simulation studies have indicated that the inclusion of such non-contributing regions as fMRI priors have only little effect on the EEG and MEG source estimates [Ahlfors and Simpson, 2004; Im et al, 2005; Liu et al, 1998]. …”
Section: Discussionmentioning
confidence: 99%
“…The reduction in the signal-to-noise ratio per source element due to cancellation may result in some active areas being detected with fMRI but not with EEG or MEG. This appears not to be a serious problem, however, for approaches in which fMRI is used to suggest likely locations for the EEG and MEG sources: simulation studies have indicated that the inclusion of such non-contributing regions as fMRI priors have only little effect on the EEG and MEG source estimates [Ahlfors and Simpson, 2004; Im et al, 2005; Liu et al, 1998]. …”
Section: Discussionmentioning
confidence: 99%
“…In a number of studies it has been shown that not all activity visible in MEG also results in BOLD responses, and vice versa (e.g. Liu et al, 1998;Schulz et al, 2004;Im et al, 2005). This has resulted in the notion of so-called fMRI-blind EEG/MEG sources and EEG/MEG-blind fMRI sources (Ritter and Villringer, Fig.…”
Section: Separate Eeg-fmri Recordings and Analyses And Subsequent Comentioning
confidence: 96%
“…However, it is likely that some EEG/MEG correlates of cognitive processing may not result in measurable changes of the BOLD signal, whereas other patterns of neuro-cognitive activity may be detectable with fMRI but not EEG (Liu et al, 1998;Nunez and Silberstein, 2000;Schulz et al, 2004;Im et al, 2005). Accordingly, a main goal of simultaneous EEGfMRI is to shed light on the foundations of the two measures and their interrelations.…”
Section: Introductionmentioning
confidence: 95%
“…Since we already identified from previous studies and our fMRI studies that the EEG sources related to the early visual process would appear around the visual cortex, we gave the source points located around occipital lobe a higher probability to be estimated in the EEG inverse. We imposed the probability to the EEG inverse solution by giving different weighting values to the diagonal terms of R. If a source belonged to the predetermined regions, 1 was multiplied by its corresponding diagonal term; otherwise, 0.1 was multiplied (Liu et al, 1998, Im et al, 2005b. The area where the functional constraints were imposed was large enough to cover the entire human visual cortex (e.g.…”
Section: Eeg Cortical Source Imagingmentioning
confidence: 99%